Fully automatic extraction of morphological traits from the web: Utopia or reality? - Diego Marcos; Robert van de Vlasakker; Ioannis N. Athanasiadis; Pierre Bonnet; Hervé Goëau; Alexis Joly; W. Daniel Kissling; César Leblanc; André S. J. van Proosdij; Konstantinos P. Panousis (Applications in Plant Sciences, 2025)
Abstract Premise Plant morphological traits, their observable characteristics, are fundamental to understanding the role played by each species within its ecosystem; however, compiling trait information for even a moderate number of species is a demanding task that may take experts years to accomplish. At the same time, online species descriptions contain massive amounts of information about morphological traits, but the lack of structure makes this source of data impossible to use at scale. Methods To overcome this, we propose to leverage recent advances in large language models and devise a mechanism for gathering and processing plant trait information in the form of unstructured textual descriptions, without manual curation. Results We evaluate our approach by automatically replicating three manually created species–trait matrices. Our method found values for over half of all species–trait pairs, with an F1 score of over 75%. Discussion Our results suggest that large‐scale creation of structured trait databases from unstructured online text is now feasible due to the information extraction capabilities of large language models. However, the process is currently limited by the availability of textual descriptions that cover all traits of interest.